Determinants of Company Employee Performance PT. Kilang Pertamina International (PT. KPI) - Fernandus Fendy Rianto; Justine Tanuwijaya (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
In the world of work and business, an employee is faced with demands for high work performance that is always able to make the best contribution to the progress of a company, namely by increasing the performance of the company’s employees. Therefore, this study aims to determine several factors that lead to an increase in employee performance. This study uses quantitative methods. This research is a cross-sectional study on employees of PT Kilang Pertamina International (PT. KPI) located in Refinery Unit (RU) II Dumai, RU III Plaju, RU IV Cilacap, RU V Balikpapan, RU VI Balongan, and RU VII. In this study, the analytical tool that can be used to analyze each variable is SEM-PLS. The results of this study indicate that to improve the performance of its employees, companies must be able to improve several aspects such as increasing emotional intelligence and self-efficacy which are oriented towards increasing company commitment. High corporate commitment from employees will be able to increase employee job satisfaction and have the potential to improve their performance. This research is expected to provide knowledge about the influence of emotional intelligence and self-efficacy that affect employee performance which leads to company and industry performance.